55 Apparent absorption, zinc retention and nutrient digestibility in lambs during an adrenocorticotropic hormone challenge. - VanValin, K (J Anim Sci, 2018)
This study sought to determine if Zn supplementation would increase Zn retention and nutrient digestibility in lambs exposed to adrenocorticotropic hormone. Twenty-two crossbred poly-pay wethers (n = 5–6/treatment) enrolled in a previous trial had been stagger started on a common diet (22 mg Zn/kg DM) for 52-d, and were placed in metabolism crates for 15-d of dietary treatments: CON: common diet + no supplemental Zn; ZINC: CON + 40 mg/d ZnSO(4) top dressed daily in fine ground corn. On d16 lambs were assigned within diet to injected challenge treatments: Saline: 2 mL saline; ACTH: 80 IU adrenocorticotropic hormone. On d17 lambs were placed in crates to facilitate fecal and urine collection, and received injections at 0700h for d17-20. Plasma cortisol was assessed on d16 3h post-feeding, and 3h after injections 1 (d17) and 4 (d20). Data were analyzed as a 2 × 2 factorial; no interactions were found (P ≥ 0.09). Plasma cortisol was greater in ACTH post-injection 1 and 4 (P ≤ 0.002). Zinc intake was greater in ZINC (P < 0.001). Zinc apparent absorption was greater in CON (16.0) vs. ZINC (7.04%; P = 0.002) and tended (P = 0.12) to be lesser in ACTH (9.57%) vs. Saline (13.5%). Day-20 plasma Zn was lesser in CON (0.67) vs. ZINC (0.78 mg/L; P = 0.03). Digestibility was greater in CON vs. ZINC for NDF (45.8% vs. 41.8%) and ADF (33.3% vs. 26.7%; P ≤ 0.03). Dry matter and OM digestibility tended (P ≤ 0.09) to be greater in CON compared to ZINC. Retained Zn was unaffected (P ≥ 0.24) by diet (CON: 4.09 mg/d; ZINC: 4.29 mg/d) or injection (Saline: 4.79 mg/d; ACTH: 3.59 mg/d) suggesting that Zn requirements in lambs may not increase in response to ACTH. Nutrient digestibility may also be affected by supplementation with ZnSO(4).